2020
DOI: 10.3390/nano10102000
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Modified Metal–Organic Frameworks, NH2-Fe-MIL-101, as pH-Sensitive Nanocarriers for Controlled Pesticide Release

Abstract: Recently, metal–organic frameworks (MOFs) have become a dazzling star among porous materials used in many fields. Considering their intriguing features, MOFs have great prospects for application in the field of sustainable agriculture, especially as versatile pesticide-delivery vehicles. However, the study of MOF-based platforms for controlled pesticide release has just begun. Controlled pesticide release responsive to environmental stimuli is highly desirable for decreased agrochemical input, improved control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…A previously published method was adopted to generate PDA-coated CUR-Zn-MOFs, with minor changes (Shan et al., 2020 ). Briefly, 19 mg of dopamine was dissolved in a Tris buffer solution (10 mM, pH 8.5) while stirring.…”
Section: Methodsmentioning
confidence: 99%
“…A previously published method was adopted to generate PDA-coated CUR-Zn-MOFs, with minor changes (Shan et al., 2020 ). Briefly, 19 mg of dopamine was dissolved in a Tris buffer solution (10 mM, pH 8.5) while stirring.…”
Section: Methodsmentioning
confidence: 99%
“…In a later study by Shan et al, 67 controlled release properties were enhanced by the elimination of burst effects, by integrating diniconazole-loaded NH 2 -MIL-101 with polydopamine (PDA). Loading of diniconazole into the amine-functionalized NH 2 -MIL-101 was performed at a ratio of 1:1 in dichloromethane at room temperature, achieving a loading of 28% by weight.…”
Section: Mofs For Pesticide Deliverymentioning
confidence: 99%
“…It has been widely used in material storage, separation, purification, catalysis, sensing, biological imaging, energy storage, and drug delivery. Compared with traditional materials, MOFs have many unique properties in drug delivery systems. The large porosity, high porosity, and huge specific surface area of MOFs contribute to improved drug loading efficiency, while its easy surface functionalization, good stability, and biocompatibility further expand its availability. , Based on the extensive research of MOFs in drug delivery and biomedicine, MOF-based multifunctional PDS has attracted more and more attention in recent years. For example, Shan et al synthesized a Fe-based MOF (NH 2 -Fe-MIL-101) for diniconazole (Dini) delivery. They found that the NH 2 -Fe-MIL-101 nanocarrier exhibited a good pesticide loading effect, with a loading rate of 28.1% for Dini.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the NH 2 -Fe-MIL-101 nanocarrier exhibited a good pesticide loading effect, with a loading rate of 28.1% for Dini. After surface modification of polydopamine, this PDS exhibits pH responsive controlled release performance . UiO-66 is a Zr-based MOF with excellent stability and high pesticide loading capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation